How the Organic Food System Supports Sustainable Diets and Translates These into Practice - Strassner, Carola; Cavoski, Ivana; Di Cagno, Raffaella; Kahl, Johannes; Kesse-Guyot, Emmanuelle; Lairon, Denis; Lampkin, Nicolas; Løes, Anne-Kristin; Matt, Darja; Niggli, Urs; Paoletti, Flavio; Pehme, Sirli; et al. (Frontiers in Nutrition, 2015)
Organic production and consumption provide a delineated food system that can be explored for its potential contribution to sustainable diets. While organic agriculture improves the sustainability performance on the production side, critical reflections are made on how organic consumption patterns, understood as the practice of people consuming significant amounts of organic produce, may also be taken as an example for sustainable food consumption. The consumption patterns of regular organic consumers seem to be close to the sustainable diet concept of FAO. Certain organic-related measures might therefore be useful in the sustainability assessment of diets, e.g., organic production and organic consumption. Since diets play a central role in shaping food systems and food systems shape diets, the role of organic consumption emerges as an essential topic to be addressed. This role may be based on four important organic achievements: organic agriculture and food production has a definition, well-established principles, public standards, and useful metrics. By 2015, data for organic production and consumption are recorded annually from more than 160 countries, and regulations are in force in more than 80 countries or regions. The organic food system puts the land (agri-cultura) back into the diet; it is the land from which the diet in toto is shaped. Therefore, the organic food system provides essential components of a sustainable diet.